Implementing business and human rights norms in Africa : law and policy interventions - Abe, Oyeniyi (London ; New York : Routledge, 2022)
"This book examines the contemporary and contentious question of the critical connections between business and human rights, and the implementation of socially responsible norms in developing countries, with particular reference to Kenya, Nigeria, and South Africa. Business enterprises and transnational corporate actors operate in a complex global environment, especially when operating in high risks sectors such as oil and gas, mining, construction, banking, and health care amongst others. Understanding human rights responsibilities, impacts and socially responsible behaviour for companies is therefore an essential component of corporate risk management in our current world. The release of the United Nations Guiding Principles on Business and Human Rights, an instrument consisting of 31 principles on this issue, has further underscored the emergence of a rapidly developing set of international law norms on human rights responsibilities of businesses and transnational corporations. It has also shaped the discourse on corporate accountability for human rights. In addition to minimizing litigation, financial and reputational risks, understanding and demonstrating corporate respect for human rights is vital to building a culture of trust and integrity amongst local communities, investors, and shareholders. This book examines, clarifies, and unpacks the guiding principles of a rights-based approach to development and social inclusion. It offers an exposition of regulatory capacity, institutional efficacy and democratic legitimacy of governance institutions that shape development including an analysis of how states are shaping business and human rights discourses locally to develop a critical understanding of identified issues by exploring the latest theories through comparative lenses"--
Introduction -- Nature and scope of business and human rights challenges in Africa -- Corporate governance paradigms and regulatory framework -- Corporate duty to respect human rights -- Integrating a rights-based approach to developmental projects -- Access to effective judicial and non-judicial remedies -- Policy and legal framework in Nigeria -- Policy and legal framework in South Africa -- Policy and legal framework in Kenya -- The future of business and human rights in Africa.
Keywords: Social responsibility of business -- Law and legislation -- Kenya; Social responsibility of business -- Law and legislation -- Nigeria; Social responsibility of business -- Law and legislation -- South Africa; Human rights -- Kenya; Human rights -- Nigeria; Human rights -- South Africa; LAW / General